CatDog : the complete series [videorecording (DVD)] (Shout! Factory, 2014)
"Brothers Cat and Dog couldn't be more different -- Cat is clever and cultured, while Dog is naïve but loveable goofball. But they definetly share one thing in common: a body! This crazy set of conjoined twins find themselves in all sorts of silly adventures, but through them all, the two misfits stick together...whether they like it or not!" --container